Pengaruh Harga dan Kualitas Pelayanan Terhadap Loyalitas - Utami, Hawi Rizqi; Wahono, Budi; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the influence of price and service quality on customer loyalty, with customer satisfaction as an intervening variable, at Hepimart Ngawi. In an era of global economic uncertainty, supermarkets must focus on delivering value and satisfaction to retain a loyal customer base. The study finds that price significantly and directly affects both customer satisfaction and loyalty. Service quality also has a positive and significant effect on customer satisfaction and loyalty. Furthermore, customer satisfaction positively influences customer loyalty. However, the results show no significant indirect effect of service quality on loyalty through satisfaction. These findings suggest that while price and service quality are crucial in building satisfaction and loyalty, satisfaction does not act as a mediator between service quality and loyalty in this context. Keywords: Price, Servicey Quality, Customer Loyalty, Customer Satisfaction